Online Dispute Resolution New Challenges - Vicente, Dário Moura; Oliveira, Elsa Dias; de Almeida, João Gomes (2022)
Online Dispute Resolution - New Challenges is a book that concerns a very current subject with practical repercussions: the use of the Internet in dispute settlement mechanisms, including arbitration, court litigation, and mediation. The book is divided into three chapters, covering the following subjects: "Due process guarantees and Online dispute resolution", "Online trial hearings - in particular, evidence" and "Confidentiality, privacy and security". All essays are written by well-known arbitrators, academics, lawyers and judges. Each essay seeks to provide the perspective of a different group of stakeholders in respect of the areas in which online dispute resolution is currently resorted to. The editors of the book are Professors at the Law School of the University of Lisbon whose fields of research include, among other topics, international arbitration, litigation and mediation. With contributions by António Abrantes Geraldes, Paula Costa e Silva, Madalena Dinis Ayala, Diego Fernandez Arroyo, Marc Henry, Catarina Monteiro Pires, Pilar Perales Viscasillas, Luís Filipe Pires de Sousa, Sofia Ribeiro Mendes, Juan Serrada Hierro, Joana Soares Correia, Bruno Sousa Rodrigues and Riu Vouga.